Effects of urban pollution on hematological parameters and defensive capacity of rainbow trout from the Chalhuanca River - Meléndez Flores, Keyro Alberto (Revista de Ciências Agroveterinárias, 2024)
Rainbow trout is essential in the Andean diet, especially in communities where water quality is essential for their health and growth. Our research focuses on how the environmental conditions of the Chalhuanca River affect the physical health, chronic stress, and immunological capacity of rainbow trout, and what the relationship of these effects is to food security in local communities. Juvenile trout from the Chalhuanca River were examined, collecting 36 samples at three points: before Cotaruse, after Caraibamba and passing Chalhuanca. The fish were measured, weighed and blood was drawn to evaluate components such as red and white blood cells, hemoglobin, hematocrit, glucose and cortisol. The ability of the fish to combat the E. coli bacteria was also analyzed and physicochemical and microbiological parameters of the water were measured. The results showed significant differences in trout health between areas. Chalhuanca trout presented worse body condition and hypochromic microcytic anemia (hemoglobin: 6.1 g/dL, hematocrit: 29%). Furthermore, a high proportion of chronic stress was observed in this area. Water quality also showed variations, with higher concentrations of fecal coliforms (1200 CFU/100 mL) and lower levels of dissolved oxygen (4.5 mg/L) in Chalhuanca, indicating a higher degree of contamination.